Staining ability of herbal tea preparations on a nano-filled composite restorative material – an in-vitro study [version 2; peer review: 2 approved] - Kalyana Chakravarthy Pentapati; Raj Kumar Narkedamalli; Vidya Saraswathi Muliya (F1000Research, 2023)
Background: Discoloration of tooth-colored restorations due to various factors is one of the principal causes behind the failure of aesthetics. There has been an surge in the consumption of herbal beverages in recent times and the dietary factors play a potential role in the discoloration tooth-coloured restorations. This study was done to juxtapose the staining ability of green tea (GT), moringa tea (MT), and hibiscus tea (HT) on a nano-filled composite restorative material. Methods: The study was conducted in-vitro on composite samples prepared using moulds. 112 discs were prepared from FiltekTM Z350XT composite using a brass mould lined with mylar strips. Samples were divided into GT, MT, HT, and artificial saliva (AS) groups and immersed in freshly prepared beverages for 15 minutes each day for 45 days. Digital reflectance spectrophotometer was utilized to record color at baseline, 30, and 45 days. Repeated-measures ANOVA with a post-hoc Bonferroni test was used to compare groups within each group. ANOVA with a post-hoc Games Howell test was used to compare mean differences in ΔE among the groups. Results: Maximum discoloration was observed in the GT, followed by HT and MT, with the least being in the AS group at the end of 30 and 45 days (P<0.001 and P<0.001) respectively. Conclusions: The universal nano-filled composite material showed clinically detectable discoloration when exposed to Green Tea, Hibiscus Tea, and Moringa Tea which increased with time. Herbal beverages have the potential to cause discoloration of the composite resin which is often the choice of material for anterior aesthetic restorations.